UPAYA PENINGKATAN PENGETAHUAN MASYARAKAT TENTANG PENCEGAHAN HIPERTENSI DESA MUNTOI KABUPATEN BOLAANG MONGONDOW - Ake R. C. Langingi; GraceI. V. Watung; Finni F. Tumiwa; Pricilya M. Warwuru; Siska Sibua (Jurnal Salam Sehat Masyarakat (JSSM), 2020)
Hypertension is a public health problem in the world both developed and developing countries. Health problems that need attention in Muntoi Village, Passi District, Bolaang Mongondow District, one of which is hypertension. The purpose of this community service activity is to increase the knowledge, attitudes and behavior of people related to hypertension in the hope of preventing the increase in hypertension in Muntoi Village, Passi District Bolaang Mongondow Regency. The method applied in the program of service activities is the lecture method with health promotion media in the form of leaflets about hypertension. The service activities in November and December 2019, followed by monitoring and evaluation activities in January 2020. The results of this activityinclude the stages of planning, implementation, monitoring and evaluation. Based on the results of dedication, there are still many people diagnosed with hypertension but do not treat or still many residents who do not know whether he was diagnosed with hypertension or not. This is the basic for community service activities to increase knowledge of attitudes and preventive behaviors to reduce the risk of hypertension at the service locations. It is expected that the public health centre or non-communicable disease program holders (hypertension) will be more active in promoting and preventing activities in the community of Muntoi Village